Positioning System of Underground Coal Mines Based on ZigBee Technology - Zhang De; Li Gang Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The study introduces the man and machine positioning system of underground coal mines based on the ZigBee Wireless Communication Technology. It can realize the effective management of the precise positioning of machine and the workers. This article presents the composition of the system, the performance and management of content and network formation. The actual application shows that the underground man-machine positioning system based on ZigBee technology can play an important role in the underground personnel information and security management. So the system can meet the needs of the mine safety management and there has great application prospect. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4039